2019
DOI: 10.12659/msm.919046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes Using Co-Expression Network Analysis in Breast Cancer as a Tool to Predict Different Stages

Abstract: BackgroundBreast cancer has a high mortality rate and is the most common cancer of women worldwide. Our gene co-expression network analysis identified the genes closely related to the pathological stage of breast cancer.Material/MethodsWe performed weighted gene co-expression network analysis (WGCNA) from the Gene Expression Omnibus (GEO) database, and performed pathway enrichment analysis on genes from significant modules.ResultsA non-metastatic sample (374) of breast cancer from GSE102484 was used to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…Through the research by Bu et al, the levels of GINS1 also in connected with the development of pancreatic cancer [34]. This is also con rmed by the research of Fu et al [35]. Our study indicated that the value of GINS1 in prognosis of human sarcoma was con rmed by 131 sarcoma patients.…”
Section: Discussionsupporting
confidence: 83%
“…Through the research by Bu et al, the levels of GINS1 also in connected with the development of pancreatic cancer [34]. This is also con rmed by the research of Fu et al [35]. Our study indicated that the value of GINS1 in prognosis of human sarcoma was con rmed by 131 sarcoma patients.…”
Section: Discussionsupporting
confidence: 83%
“…STRING database version 10.5 ( http://string-db.org ) was applied to evaluate the PPI information. DEGs were uploaded into STRING, a confidence score >0.9 defined them as significant [ 23 ], and then, the PPI network was constructed. We downloaded the resulting data in a table in a tab-separating values format.…”
Section: Methodsmentioning
confidence: 99%
“…The cytoHubba plug-in was used to identify the hub genes. A hub gene is defined as a gene with the highest degree of connectivity in the hub module [ 23 ]. The hub genes showed a strong association with other node proteins (more than 10) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mutations or deregulation of the human homolog of the PSF1 gene was observed in correlation with disorders involving cancer, neurodevelopmental, and immunodeficiency issues [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. However, the precise role of GINS subunits in these processes is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The study of noncatalytic proteins of the CMGE complex is attracting greater attention, because mutations in genes encoding its subunits or changes in their expression have a significant impact on the development of cancer or genetic diseases [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. In contrast to the role of DNA polymerases, which have been analyzed in detail, the influence of the noncatalytic components of the replisome on the DNA replication process remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%